Application of Simplified Neutral Point Clamped Multilevel Converter in a Small Wind Turbine - Mlodzikowski, Pawel; Milczarek, Adam; Malinowski, Mariusz (Electrical, Control and Communication Engineering, 2014)
In low power distributed generation systems low cost together with the energy quality requirements are a key element. It is known that quality of voltage waveforms generated from multilevel converters is better in comparison with those from two-level. Due to advancements in power electronics and microcontrollers, multilevel converters are being built with the use of integrated power modules thus this type of converters are getting more compact in size. This paper investigates performance of a derivation from the most popular multilevel topology - a neutral point clamped converter (NPC). Applying the idea for simplifying the topology by reducing the number of switches (what came from drives) this NPC converter is capable of bidirectional AC/DC/AC operation. For the AC/DC part two schemes are tested: Direct Torque Control Space Vector Modulated and Field Oriented Control but for the DC/AC part a control scheme utilizing the proportional-resonant controller was chosen. Laboratory setup was based on a permanent magnet synchronous generator with control and acquisition completed with the help of dSpace 1005 control box. Experimental verification shows that system operates properly.